On the choice of the appropriate AES data encryption method for ZigBee nodes. Issue 2 (7th December 2010) - Ottoy, G.; Hamelinckx, T.; Preneel, B.; De Strycker, L.; Goemaere, J.‐P.
Abstract: This paper describes the experiments that have been conducted to determine the optimal implementation method for AES (Advanced Encryption Standard) data encryption in a ZigBee network in terms of energy consumption. Four possible scenarios have been considered. The first one is a freely available AES‐cryptographic algorithm on the processor which controls the ZigBee nodes. The second also involves the processor but is based on a proprietary, highly optimized algorithm. The other methods are based on hardware implementations. Whereas the third option is based on a cryptographic block, embedded in the ZigBee node controller, the last solution utilizes an AES128‐CBC‐MAC hardware co‐processor embedded on a Spartan 3A FPGA. The ZigBee modules in the network contain an 8‐bit microcontroller which takes care of the ZigBee protocol stack—and the encryption calculations in all but the last case. All approaches are examined and compared. We show that the usage of a microcontroller with an on‐board AES processor is the optimal design choice for a new hardware platform. An optimized software library gives the best results when extending an existing platform. This paper gives developers an idea of the amount of energy they can gain/lose by choosing one of the four solutions. Copyright © 2010 John Wiley & Sons, Ltd. Abstract : The ZigBee specification applies the Advanced Encryption Standard (AES) for securing wireless transmissions. However, it is not specified how ZigBee modules should perform the encryption. This paper investigates the different possibilities on how to implement AES128‐CBC‐MAC data encryption on a ZigBee module and weighs the advantages and disadvantages of different approaches, keeping in mind that different developers can have different needs (fast implementation, small footprint, low power consumption, etc).